Thermal conductivity of sandwich panels made with synthetic and vegetable fiber vacuum-infused honeycomb cores. (January 2017) - Vitale, Juan P; Francucci, Gaston; Stocchi, Ariel
Building, naval, and automotive industries have deep interest in eco-friendly, lightweight, stiff and strong materials. In addition, materials with low thermal conductivity are desirable in many applications where energy savings and thermal comfort are needed. In response to these requirements, sandwich panels were manufactured using glass and jute fiber composite skins bonded to different cores: balsa wood, Divinycell® and honeycombs. These honeycombs, as well as the skins, were manufactured by the vacuum infusion technique using polyester resin and jute, glass and carbon fiber fabrics. In this work, the thermal properties and density of the sandwich panels were measured and compared.